Donor‐Transmitted Cancers in Transplanted Livers: Analysis of Clinical Outcomes. Issue 1 (15th September 2020) - Eccher, Albino; Girolami, Ilaria; Marletta, Stefano; Brunelli, Matteo; Carraro, Amedeo; Montin, Umberto; Boggi, Ugo; Mescoli, Claudia; Novelli, Luca; Malvi, Deborah; Lombardini, Letizia; Cardillo, Massimo; et al.
Abstract : The risk of transmission of malignancy from donor to recipient is low. However, this occurrence has dramatic consequences. Many reports of donor‐derived cancers in liver transplant recipients have been published, but they have not been systematically summarized into a lucid and unified analysis. The present study is an attempt to provide clarity to this unusual but clinically important problem. We systematically reviewed all patient reports, patient series, and registries published on cancer transmission events through the end of December 2019. We identified a total of 67 publications with 92 transmission events. The most frequently transmitted cancers were lymphomas (30; 32.6%), melanomas (8; 8.7%), and neuroendocrine tumors (8; 8.7%). Most of the melanomas were metastasizing, whereas most of the lymphomas were localized to the graft. The median time to cancer diagnosis after transplantation was 7 months, with 78.1% of diagnoses established in the first year. Melanoma carried the worst prognosis, with no recipients alive at 1 year after cancer diagnosis. Lymphoma recipients had a better outcome, with more than 75% surviving at 2 years. A metastatic cancer carries a worse prognosis for recipients, and recipients with localized cancer can benefit from the chance to undergo transplantation again. The findings confirm the need to pay attention to donors with a history of melanoma but also suggest the need for a more careful evaluation of groups of donors, such as those dying from cerebral hemorrhage. Finally, recipients of organs from donors with cancer should be carefully followed to detect potential transmission. Abstract : https://www.wileyhealthlearning.com/Activity/7225312/disclaimerspopup.aspx